Use of non-pharmacological methods for pain relief during normal labor: an integrative literature review (Research, Society and Development, 2022)
It is important to highlight that the subject pain relief in normal labor carries with it a brief history about the occurrence of labor in society. In this context, the present research aims to identify the use of non-pharmacological methods for pain relief during normal labor. Therefore, an integrative literature review was conducted, which is an investigative method that allows the collection, critical analysis and synthesis of available information on the topic in question. Thus, it is noted that there are several known non-pharmacological methods that favor the reduction of pain during labor, and that these have quite variable prevalence of use. Therefore, it is suggested that the incentive to humanize childbirth practices be intensified, especially regarding the use of non-pharmacological measures.